2007
DOI: 10.1107/s0108270107029721
|View full text |Cite
|
Sign up to set email alerts
|

Two different modes of halogen bonding in two 4-nitroimidazole derivatives

Abstract: In the crystal structures of the two imidazole derivatives 5-chloro-1,2-dimethyl-4-nitro-1H-imidazole, C(5)H(6)ClN(3)O(2), (I), and 2-chloro-1-methyl-4-nitro-1H-imidazole, C(4)H(4)ClN(3)O(2), (II), C-Cl...O halogen bonds are the principal specific interactions responsible for the crystal packing. Two different halogen-bond modes are observed: in (I), there is one very short and directional C-Cl...O contact [Cl...O = 2.899 (1) A], while in (II), the C-Cl group approaches two different O atoms from two different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…The N1-H1AÁ Á ÁO4 and N1-H1CÁ Á ÁO4 ii hydrogen bonds [symmetry code: (ii) x, y + 1, z], along with O2-H2DÁ Á ÁO3 ii , form a chain of edgefused R 3 3 (10) ring motifs extending along the [010] direction, as observed in the structure of 3-acetylanilinium dihydrogen phosphate (Cinčić & Kaitner, 2008). The ClÁ Á ÁO1 interaction, which acts as a pseudo-hydrogen bond (Bryant et al, 1998;Kubicki & Wagner, 2007), with the Cl1 atom at (x, y, z) as donor and atom O1 at (Àx + 1 2 , Ày + 1 2 , Àz + 1 2 ) as acceptor, along with the N-HÁ Á ÁO hydrogen bonds, forms a chain of fused R 2 4 (10) motifs extending along the [010] direction. The 2 1 screw-related chains of R 3 3 (10) and R 2 4 (10) motifs along ( 1 4 , y, 1 4 ) ( Fig.…”
Section: Commentmentioning
confidence: 99%
“…The N1-H1AÁ Á ÁO4 and N1-H1CÁ Á ÁO4 ii hydrogen bonds [symmetry code: (ii) x, y + 1, z], along with O2-H2DÁ Á ÁO3 ii , form a chain of edgefused R 3 3 (10) ring motifs extending along the [010] direction, as observed in the structure of 3-acetylanilinium dihydrogen phosphate (Cinčić & Kaitner, 2008). The ClÁ Á ÁO1 interaction, which acts as a pseudo-hydrogen bond (Bryant et al, 1998;Kubicki & Wagner, 2007), with the Cl1 atom at (x, y, z) as donor and atom O1 at (Àx + 1 2 , Ày + 1 2 , Àz + 1 2 ) as acceptor, along with the N-HÁ Á ÁO hydrogen bonds, forms a chain of fused R 2 4 (10) motifs extending along the [010] direction. The 2 1 screw-related chains of R 3 3 (10) and R 2 4 (10) motifs along ( 1 4 , y, 1 4 ) ( Fig.…”
Section: Commentmentioning
confidence: 99%
“…In the seminal paper by Laurence et al, bifurcated halogen bonds are found to be unlikely for any strong (inorganic) halogen donor, while it may be possible for weaker halogen bond donors (which will form less covalent bonds) to form symmetric halogen bonds. Indeed, numerous experimental (in particular with heterocycles and nitro groups as acceptors) and theoretical studies have shown the existence of bifurcated halogen bonds. However, in the vast majority of cases the bifurcated halogen bonds show pronounced asymmetry, one contact being shorter and straighter and the other longer and more bent.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the difficulty in obtaining positively charged 4,5dicyano-2-halo-imidazolium compounds, given the results discussed above, it appeared likely that the neutral heterocycle could be sufficiently electron-withdrawing to induce a σ hole on the polarizable halogen, and thus provide a new uncharged motif for halogen bond formation. Such interactions have been observed in both 2-and 5-chloro-1-methyl-4-nitroimidazole, 35 which is, in principle, less favorably disposed to halogen bond formation than 2-bromo-4,5-dicyanoimidazole, possessing fewer electron-withdrawing groups and a less polarizable halogen. Single crystals suitable for X-ray diffraction were obtained for 2-bromo-4,5-dicyanoimidazole to examine its hydrogen bonding behavior, and for its N-benzyl derivative to provide a second perspective on any halogen-bonding properties.…”
Section: ■ Results and Discussionmentioning
confidence: 99%